Blood-based liquid biopsy: Insights into early detection and clinical management of lung cancer. (1st January 2022) - Liu, Cuiliu; Xiang, Xiaoqiang; Han, Shuangqing; Lim, Hannah Ying; Li, Lingrui; Zhang, Xing; Ma, Zhaowu; Yang, Li; Guo, Shuliang; Soo, Ross; Ren, Boxu; Wang, Lingzhi; et al.
Abstract: Currently, early detection of lung cancer relies on the characterisation of images generated from computed tomography (CT). However, lung tissue biopsy, a highly invasive surgical procedure, is required to confirm CT-derived diagnostic results with very high false-positive rates. Hence, a non-invasive or minimally invasive biomarkers is essential to complement the existing low-dose CT (LDCT) for early detection, improve responses to a certain treatment, predict cancer recurrence, and to evaluate prognosis. In the past decade, liquid biopsies (e.g., blood) have been demonstrated to be highly effective for lung cancer biomarker discovery. In this review, the roles of emerging liquid biopsy-derived biomarkers such as circulating nucleic acids, circulating tumour cells (CTCs), long non-coding RNA (lncRNA), and microRNA (miRNA), as well as exosomes, have been highlighted. The advantages and limitations of these blood-based minimally invasive biomarkers have been discussed. Furthermore, the current progress of the identified biomarkers for clinical management of lung cancer has been summarised. Finally, a potential strategy for the early detection of lung cancer, using a combination of LDCT scans and well-validated biomarkers, has been discussed. Highlights: Liquid biopsies are slightly or non-invasive techniques for early cancer detection. Can identify many novel biomarkers in the blood, serum, or urine of patients. Help in early diagnosis and prognosis prediction in NSCLC patients. Be able to complement LDCT to form an effective platform for lung cancer screening.